Kedudukan Penyandang Disabilitas dalam Melakukan Pembuatan Perjanjian Pasca Judicial Review Pasal 433 KUHPerdata - Rafid Algiffari (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This study discusses the position of persons with disabilities, especially those with mental and intellectual disabilities, in carrying out legal actions following the judicial review of Article 433 of the Civil Code through the Constitutional Court Decision Number 93/PUU-XX/2022. Prior to this amendment, Article 433 of the Civil Code used discriminatory terms and automatically placed persons with disabilities under guardianship, thereby eliminating their legal capacity as independent legal subjects. This Constitutional Court decision changed the phrase "must be guarded" to "can be guarded" and emphasized that the placement of guardianship can only be made based on a competent medical diagnosis. The research method used is normative juridical through a statutory approach and court decisions. The results of the study show that the change in norms restores the constitutional rights of persons with disabilities, including the right to autonomy, equality before the law, and protection from discrimination. In addition, this change directly affects the requirements for capacity in making agreements according to Article 1320 of the Civil Code, so that persons with mental disabilities who have the capacity are still considered capable of acting. Therefore, this decision is an important step in realizing a legal system that is more inclusive, just and respects the dignity of people with disabilities.